Neurofeedback training protocols in sports: A systematic review of recent advances in performance, anxiety, and emotional regulation - Tosti, B.; Corrado, S.; Mancone, S.; Di Libero, T.; Carissimo, C.; Cerro, G.; Rodio, A.; da Silva, V. F.; Coimbra, D. R.; Andrade, A:; Diotaiuti, P. (Brain Sciences, 2024)
(1) Background. Neurofeedback has been used in sports since the 1990s, frequently showing positive outcomes in enhancing athletic performance. This systematic review provides an updated analysis of neurofeedback training in sports, evaluating reaction time, cognitive performance, and emotional regulation to address literature gaps and suggest future research directions.